2019
DOI: 10.3390/en12142682
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rates of Offshore Wind Transmission Systems

Abstract: In the offshore wind industry, failures are often costlier than those experienced onshore. Through examination of the literature, it is clear that failures occurring in offshore transmission systems are not well documented. As a result of this, many developers and other parties involved in the planning processes associated with offshore wind farms will defer back to existing reliability metrics in the public domain. This article presents a review of European offshore wind farm transmission failures based on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…Three typical energy delivery network topologies in the project DTOceanPlus, with the sketches shown in Figures 2-4, are used for this case study. Due to no tailor-made reliability database for marine energy converters, the failure rates of the basic components can be referred to a generic database for electrical components in other industrial applications [13,14] and also should be subject to engineering judgement. The failure rates to be used are given in Table 2.…”
Section: Case Study 41 Network Topologiesmentioning
confidence: 99%
“…Three typical energy delivery network topologies in the project DTOceanPlus, with the sketches shown in Figures 2-4, are used for this case study. Due to no tailor-made reliability database for marine energy converters, the failure rates of the basic components can be referred to a generic database for electrical components in other industrial applications [13,14] and also should be subject to engineering judgement. The failure rates to be used are given in Table 2.…”
Section: Case Study 41 Network Topologiesmentioning
confidence: 99%
“…This voltage is transformed to 155 kV AC and then converted into ±150 kV DC to feed two 125 km sea cables, which continue into two 75 km land cables, transmitting 400 MW power to the land. However, the trade-off between HVAC and HVDC solutions is still complex to determine, as besides losses, questions of reliability and architecture of the offshore grid come into the balance [36,37]. While there is a project for backing HVDC for the Norfolk Vanguard windfarm (UK, 1.8 GW), the longest cable connection in the world for an offshore windfarm has just been installed: the 200 km-long cable is powered under 220 kV HVAC [38].…”
Section: Potentialities For Hvdc and Cable Energy Transmissionmentioning
confidence: 99%
“…Additionally, separate studies have addressed the explored features of offshore wind power including the impacts of air density fluctuations, transmission systems, electrical topography, etc. [14][15][16]. It was shown that innovative solutions dealing with turbines, such as a lubrication system for hollow roller bearings, can lead to increased energy efficiency and system output [17,18].…”
Section: Introductionmentioning
confidence: 99%